2016
DOI: 10.3390/app6050128
|View full text |Cite
|
Sign up to set email alerts
|

A passively Q-switched Ho:YVO4 Laser at 2.05 μm with Graphene Saturable Absorber

Abstract: Abstract:We report a passively Q-switched Ho:YVO 4 laser pumped at 1.94 µm with multilayer graphene as a saturable absorber. At the absorbed pump power of 9.3 W, the maximum average output power of 2.2 W was obtained in Ho:YVO 4 laser with minimum pulse width of 265.2 ns and pulse repetition rate of 131.6 kHz at 2052.1 nm. In addition, a beam quality factor of M 2~1 .7 was measured at the maximum output level. This is, as far as we know, the first time that graphene has been used in a passively Q-switched Ho:Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Recently, many two-dimensional (2D) materials such as graphene, [7] transition metal disulfides, [8][9][10][11] and topological insulators [12] were employed as the saturable absorber (SA) to achieve Q-switching thulium (Tm) or holmium (Ho)doped lasers at 2-µm. Compared with the above materials, black phosphorus (BP) with distinctive structure and properties [13,14] is an attractive and promising 2D material as a passive Q-switch SA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many two-dimensional (2D) materials such as graphene, [7] transition metal disulfides, [8][9][10][11] and topological insulators [12] were employed as the saturable absorber (SA) to achieve Q-switching thulium (Tm) or holmium (Ho)doped lasers at 2-µm. Compared with the above materials, black phosphorus (BP) with distinctive structure and properties [13,14] is an attractive and promising 2D material as a passive Q-switch SA.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 2D materials, graphene is a 2D sheet of sp2-bonded carbon atoms with a honeycomb lattice [13]: this has attracted attention from workers in many disciplines, especially as it has special capabilities with regard to nonlinear saturable absorption. Graphene has very good thermal conductivity and optical properties, due to its zero-bandgap structure, and pure non-defective single-layer graphene with a thermal conductivity of up to 5300 W/m•K and its optical absorption is decided, independent of optical frequencies and optical conductivity constants [14]. Therefore, graphene is used as an SA in fiber and solid-state laser devices at a 1-2 µm wavelength range to achieve stable PQS and mode-locked laser emissions, owning to its ultrafast recovery time and moderate modulation depths [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has very good thermal conductivity and optical properties, due to its zero-bandgap structure, and pure non-defective single-layer graphene with a thermal conductivity of up to 5300 W/m•K and its optical absorption is decided, independent of optical frequencies and optical conductivity constants [14]. Therefore, graphene is used as an SA in fiber and solid-state laser devices at a 1-2 µm wavelength range to achieve stable PQS and mode-locked laser emissions, owning to its ultrafast recovery time and moderate modulation depths [14][15][16][17][18]. Loiko et al have demonstrated that a PQS mode of Ytterbium lasers with a graphene SA possessing a 1.9-µJ pulse energy and a 190-ns pulse duration were achieved from Yb-doped calcium niobium gallium garnet disordered garnet crystal [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations